2050. Effect of a Stewardship Intervention on Post-Prescriptive Antibiotic Timeouts in Nursing Homes - Liao, Chi-Yin (Open Forum Infect Dis, 2019)
BACKGROUND: Antibiotic overuse and misuse is a common problem in nursing homes (NHs). Meaningful improvements in the quality of antibiotic prescribing in NHs may be improved through post-prescriptive interventions (antibiotic timeouts) focused on stopping, streamlining and/or shortening ongoing antibiotic treatments. A recently completed trial of a complex antibiotic stewardship intervention provided us with an opportunity to explore to what extent NH providers engaged in antibiotic timeouts at baseline and the effects of the intervention on these behaviors. METHODS: Data on antibiotic prescriptions in 11 NHs (6 intervention, 5 control) were collected for 12 months prior and 13 months after intervention introduction. We categorized antibiotic change events (ACEs) as: (1) changes in dose, frequency, or route for the same antibiotic, (2) change to another antibiotic with different spectrum, and (3) early discontinuation (stopped after 2 days or less). Modifications considered to be routine (e.g., Azithromycin dose reduction from 500 to 250 mg) were not considered a meaningful ACE. Frequency of ACEs both overall and by type were compared using a difference in difference (DID) approach. RESULTS: Of 2647 NH initiated antibiotic events, 376 (14.2%) were modified over the study period. The most common type of modification was a change in spectrum (n = 241, 64.1%) followed by early discontinuation of the antibiotic (n = 118, 31.4%). The difference in ACEs before and after the intervention as well as DID estimates are detailed in the Table. CONCLUSION: The antibiotic stewardship intervention did not impact total ACEs but did appear to increase the frequency of discontinuation ACEs. An inability to capture data on shortening ACEs (e.g., reducing a treatment course from 14 to 7 days) was a limitation of this study. Additional research on how to foster more frequent and effective antibiotic timeouts in NHs is needed. [Image: see text] DISCLOSURES: All authors: No reported disclosures.